2021
DOI: 10.3389/fspor.2021.685286
|View full text |Cite
|
Sign up to set email alerts
|

Playing Minecraft Improves Hippocampal-Associated Memory for Details in Middle Aged Adults

Abstract: Concerns are often raised about the impact that playing video games may have on cognition and behavior, whether gameplay is intense and protracted as with competitive Esports or whether it is more casual gameplay. Work in our lab and others, however, has shown that at least some classes of games can improve memory function. In particular, playing immersive 3D games that provide rich experiences and novelty improve memory on tasks that rely upon the hippocampus in effects that mirror the effects of “environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…While video games have commonly been used in scientific research to train, intervene, and assess various cognitive abilities and brain processes ( 42 45 ), here we used the video game Minecraft as a platform for remote, behavioral research. Previously, the video game Minecraft was used as a proxy for environmental enrichment in humans and used to observe individual exploratory behaviors ( 46 48 ). Our ability to create a task to disentangle the contributions of sleep to spatial memory and navigation are further testament to the game’s potential in studying naturalistic, ecologically valid cognitive processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While video games have commonly been used in scientific research to train, intervene, and assess various cognitive abilities and brain processes ( 42 45 ), here we used the video game Minecraft as a platform for remote, behavioral research. Previously, the video game Minecraft was used as a proxy for environmental enrichment in humans and used to observe individual exploratory behaviors ( 46 48 ). Our ability to create a task to disentangle the contributions of sleep to spatial memory and navigation are further testament to the game’s potential in studying naturalistic, ecologically valid cognitive processes.…”
Section: Discussionmentioning
confidence: 99%
“…Second, while Minecraft is not entirely open source, it can be customized and modified to track users movements, activities, and actions, as well as create tasks within the world of Minecraft. Lastly, Minecraft can be played remotely on custom servers ( 47 , 48 ) that can track a significant amount of information about users’ behaviors and contexts. Remote and accessible testing platforms could be helpful for exploring sleep-dependent cognition; however, they are currently underutilized.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, gaming was shown to be effective also as a therapy against mental disorders, such as attention deficit hyperactivity disorder (ADHD) [ 55 , 56 , 57 , 58 ]. Recent interesting papers showed how playing Minecraft [ 59 ] or SuperMario [ 60 ] were associated with an improvement of hippocampal-associated memory [ 59 ].…”
Section: Esports Health Problemsmentioning
confidence: 99%
“…In several prior interventional studies using young (Clemenson and Stark, 2015 ; Clemenson et al, 2019 ), middle-aged (Stark et al, 2021 ), and older adults (Clemenson and Stark, 2017 ; Kolarik et al, 2020 ; Wais et al, 2021 ), the MST’s LDI metric has shown no clear sign of practice effects. Yet, at least in the version used by CogState, at least two studies have shown not only practice effects (Papp et al, 2020 ) but the potential predictive power of such effects in diagnosing clinical cognitive decline (Jutten et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The traditional version of the MST has been freely available in several formats (stand-alone and online) on GitHub 1 . In prior work (Stark et al, 2021 ), we created an online version of the MST using the open-source jsPsych library for web-based deployment (de Leeuw, 2015 ) and the open-source JATOS package (Lange et al, 2015 ) to provide a reliable means of securely administering test sessions on the web and managing the data. We utilized the same structure here.…”
Section: Methodsmentioning
confidence: 99%